Cross‐cultural differences in nurse burnout and the relationship with patient safety: An East‐West comparative study. (26th August 2021) - Fish, Jennifer A.; Sharplin, Greg; Wang, Lyu; An, Yan; Fan, Xiuzhen; Eckert, Marion
Abstract: Aims: To compare levels of nurse burnout across eastern and western cultures, as well as examine the influence of burnout on patient safety cross‐culturally. Design: Comparative cross‐sectional study. Methods: Survey data were collected from nurses between August and October 2017 in Australia ( n  = 730) and between April and October 2019 in China ( n  = 1107). Variables included burnout (emotional exhaustion, depersonalization, personal accomplishment), nurse leadership and support, staffing and resource adequacy, and perceived patient safety. Data were analysed separately for each jurisdiction using bootstrapped hierarchical regressions, which tested the relationships between burnout indicators and patient safety, controlling for support resources. Results: Emotional exhaustion and depersonalization scores were significantly higher in the Australian sample compared with the Chinese sample. Australian participants reported significantly lower patient safety grades than Chinese participants and were less likely to agree that support resources were present in their current job. Separate regressions indicated that patient safety was significantly associated with staffing and resource adequacy, nurse leadership and support, and depersonalization among Australian participants (30% of variance explained in the final regression model), while staffing and resource adequacy, nurse leadership and support, personal accomplishment and emotional exhaustion predicted patient safety for Chinese participants (22% of variance explained in the final model). Conclusion: Australian nurses are at greater risk of burnout than Chinese nurses. Burnout dimensions are differentially associated with patient safety across cultures. Culturally relevant interventions may be more optimal than universal approaches for improving burnout and patient safety in nursing. Impact: This study increased understanding of cross‐cultural differences in nurse burnout and the relationship with patient safety. Australian nurses were at greater risk of burnout than Chinese nurses. Emotional exhaustion, depersonalization and personal accomplishment influenced patient safety distinctively across the countries. These findings inform interventions designed to reduce nurse burnout and improve patient safety internationally.